Perilaku Pencarian Pengobatan dan Perawatan Mandiri pada Penderita Filariasis di Kabupaten Wonosobo - Dheo, Ruth Puspita; Masfiah, Siti; Maghfiroh, Arrum Firda Ayu (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2019)
Background: Promptly treatment is essential for filariasis patients to reduce permanent disability. Preliminary study of several filariasis patients with swollen leg in Wonosobo regency indicated as delay access to promt treatment which increase the risks of transmision as well as worsen patient’s condition. The purpose of this study was to explore health-seeking behaviour and self-care of patient in Wonosobo regency.Method: This study employs qualitative research using phenomenology approach. Five informants were selected by using criteria as patients with clinically symptomatic swelling leg and willing to participate to this study. The supporting informants were selected to family members and health workers who handle filariasis treatment. All data were analyzed by using content analysis.Results: Most filariasis patients were categorized as low income and having limited knowledge of the disease. They believed that the disease caused by curse so that medical treatment will not cure it and they have desperate with the illness. Psychosocial burden caused them feel anxiety even afraid to be outcasted. Their current condition mostly swollen legs with or without complications and the disease interferes their activity as very painful disease. Although the treatment will reduce pain, but it was only temporary, so that the patients felt that the treatment will be useless. The health seeking behaviour indicated that all patients experienced delay in accessing medical treatment, they tried to find other alternative treatment such as traditional treatment. Most patients have not yet performed good self-care as recommended by health workers. In addition, information and socialization about filariasis to patients, families and communities are limited because it has not been as priority program of health center. Health education program should be conducted to improve positive behavior of community regarding the prevention, early detection, prompt treatment and self-care of the disease.